Migrating from SAP ECC to SAP S/4 HANA : A multidimensional multiple case study analyses to identify critical success and risk factors at early adopters : A qualitative research for SAP S/4 HANA migration projects - Toprak, Mahmut (My University, 2018)
SAP decided that it will stop supporting SAP ECC by 2025 and therefore it is for organizations and especially early adopters of utmost importance to know which factors are relevant for a successful migration from SAP ECC to SAP S/4 HANA. SAP S/4 HANA is the next generation ERP system and promises to deliver great benefits, however it seems that early adopters have many difficulties on many aspects. This thesis therefore provides a multidimensional view on such projects from the following four perspectives: (1) top-management perspective; (2) project management perspective; (3) technical perspective; and (4) end-user perspective. A multiple case study with semi-structured open-ended interviews were conducted among three organizations, from which two are situated in The Netherlands and one in Switzerland. Based on the analysis of the interviews and internal doc-umentations it enabled the researcher to validate and identify the critical success factors, critical risk factors and the risk mitigation strategies per perspective and per organization. Finally, an aggregated amount of 54 critical success factors and 24 critical risk factors were considered as of great im-portance when implementing and migrating from an on-premise SAP ECC environment to an on-premise SAP S/4 HANA environment.
Keywords: Migration, Critical Success Factors, Critical Risk Factors, Risk Mitigation, Early Adopters, SAP ECC, SAP HANA, SAP Fiori, SAP S/4 HANA